Transforming the business process diagram into a class diagram by model-driven architecture - Habri Mohamed Achraf; Esbai Redouane; Lamlili El Mazoui Nadori Yasser (Institute of Advanced Engineering and Science, 2023)
The strength of the model-driven architecture (MDA) lies in its use of models and diagrams in the process of visualizing and developing information systems of companies, that is why we chose the business process model and notations (BPMN) due to the simplicity of the symbols of its diagrams and the clarity of its notations so that all simple users of information systems within the organization can understand their needs and goals quickly and smoothly. In our paper, we suggested that we connect all categories of the staff in the companies, whatever their specialty, and the IT developers, by making a transformation between the BPMN diagrams as independent computing model to the unified modeling language (UML) class diagram as platform independent model. We chose the latter as a destination due to its development and the possibility of transforming it into a powerful and integrated program, and also to complete other transformations later, we chose query views transformations (QVT) due to its consistency with the same family of programs and previous languages.